Campaign Problems: How Fans React to Taylor Swift's Controversial Political Awakening. (July 2022) - Driessen, Simone
This study examines how the fandom of pop star Taylor Swift negotiates her 'political' awakening, after politically coming-out via Instagram in 2018. When Swift announced her vote for two Democratic senators, (international) media and her fandom considered it controversial. Swift, unlike many other pop-singers, had never publicly expressed her political views, until 2018. Yet, doing so put her on the map as a potential celebrity politician (CP): a celebrity who is fighting for a particular interest or certain political outcome, while holding a certain political influence over an audience. By scrutinizing how her fandom, the "Swifties, " deal with their idol's political revelations, this study offers a granular insight into the intersection between celebrity, fandom, and political culture. Drawing on a content analysis of fan-interviews and online comments, this study illustrates how fans negotiate Swift's transition from popstar to CP. It demonstrates how fans consider Swift's political coming-out: On the one hand, they think it is a potential career-strategy of Swift, to lift her persona from singer to strategic "business" woman. On the other hand, the fans consider it a "must" for pop stars in today's political climate to express where they stand politically. This discussion highlights that the how of Swift's message, and not just the what or why, are of importance in understanding her position as a CP. Therewith, this study illustrates how fans make sense of today's politics through the celebrity persona—potentially putting an even greater burden on the shoulders of today's stars.